Stack Frames A Look From Inside - Di Cataldo, Giuseppe (Apress : Imprint: Apress, 2016)
This book teaches you exactly how program memory content and organization is vital for computer security, especially Unix-like operating systems. You will learn how it is manipulated to take control of a computer system, as well as the countermeasures that system designers set up to avoid this. Neither a guide for hackers nor an all-out theory book, this book is ideal for anyone studying computer security who wants to learn by doing. Using a practical approach, you will understand how stack frames relate to hardware and software theory and the various GNU/Linux distributions, before moving on to Base 2, 8 and 16 notations, executables and libraries. Lastly you will go in-depth to understand the intricacies of stack frames. A vital resource for all computer security students and enthusiasts, add Stack Frames: A Look Inside to your library today.